2004
DOI: 10.1134/1.1773334
|View full text |Cite
|
Sign up to set email alerts
|

Depinning at the initial stage of the resistive transition in superconductors with a fractal cluster structure

Abstract: Depinning of vortices in percolative superconductor containing fractal clusters of a normal phase is considered. Transition of the superconductor into a resistive state corresponds to the percolation transition from a pinned vortex state to a resistive state when the vortices are free to move. The motion of the magnetic flux transferred by these vortices gives rise to the region of initial dissipation on current-voltage (U-I) characteristic. The influence of normal phase clusters on distinctive features of U-I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The peculiarities of the normal phase clusters were considered in detail in papers [12][13][14][15]. In the article [8] it was found that the DC magnetic field strongly influences on the fractal dimension of the boundaries of the normal phase clusters.…”
mentioning
confidence: 99%
“…The peculiarities of the normal phase clusters were considered in detail in papers [12][13][14][15]. In the article [8] it was found that the DC magnetic field strongly influences on the fractal dimension of the boundaries of the normal phase clusters.…”
mentioning
confidence: 99%